2014
DOI: 10.3892/mmr.2014.1964
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of Lycium barbarum polysaccharides on cell apoptosis and senescence is potentially mediated by the p53 signaling pathway

Abstract: Lycium barbarum (L. barbarum) fruit or extract has been regarded as a superior-grade Chinese medicine, used to modulate body immunity and for anti-aging purposes. However, the underlying molecular mechanisms behind these effects remain unclear. In the present study, L. barbarum polysaccharides (LBPs), considered a major contributor of L. barbarum effects, were used to elucidate its mechanism of action by phenotypic and senescence associated-β-galactosidase (SA-β-gal) assays, evaluation of survival rates in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 36 publications
1
30
0
1
Order By: Relevance
“…At the moment we cannot fully rule out the possibility that some of the SaβG activity detected in developing zebrafish is related to autophagy. However, other studies which looked at senescence at specific time points in zebrafish observed identical SaβG activity to this study (Kishi et al, 2008), and this activity correlated with other markers associated with senescence such as p53 and p21 expressions (Donnini et al, 2010; Xia et al, 2014).
Fig.
…”
Section: Resultssupporting
confidence: 83%
“…At the moment we cannot fully rule out the possibility that some of the SaβG activity detected in developing zebrafish is related to autophagy. However, other studies which looked at senescence at specific time points in zebrafish observed identical SaβG activity to this study (Kishi et al, 2008), and this activity correlated with other markers associated with senescence such as p53 and p21 expressions (Donnini et al, 2010; Xia et al, 2014).
Fig.
…”
Section: Resultssupporting
confidence: 83%
“…LBP is a water-soluble polysaccharide extracted from Lycium barbarum and exerts multiple biological functions including protective effects on the male reproductive system (30). In this study, our results showed that STZ-induced diabetic rats showed impaired spermatogenic function with a decrease in PCNA, SIRT1, and HIF-1α expression and an increase in cell apoptosis in the testes.…”
Section: Discussionmentioning
confidence: 54%
“…In fact, Oh et al [6] demonstrated that LBB extract has inhibitor effect on proinflammatory mediator production in lipopolysaccharide-stimulated RAW 264.7 cells via blockade on the MAPKs and NF- κ B pathways. Additionally, in the last few years, LBBs have been described to modulate the aging by acting on cp53-mediated pathway [7] and on the resistance to the generation of lipid peroxide and other substances, which damage cell membrane lipid [8]. LBB extract has been also described for its immune enhancing [9], antioxidant and anticancer [3], and hepatoprotective and neuroprotective [10] properties.…”
Section: Introductionmentioning
confidence: 99%